Prelinguistic infants' communicative system: Role of caregiver social feedback. Issue 5 (October 2013) - Miller, Jennifer L.; Lossia, Amanda K.
Infants' prelinguistic vocalizations and gestures are rarely studied as a communicative system. As a result, there are few studies examining mechanisms of change concurrently in prelinguistic vocal and gesture behavior. Here we report the first evidence that contingent caregiver social feedback to infant gestures influences not only gesture production, but also prelinguistic vocal behavior. Study 1 demonstrates the relationship between gesture and vocal behavior in 12-month-old infants and contingent caregiver social feedback. Caregiver feedback to infant gesture production was positively associated with infant gestures, gesture–vocal combinations, and vocalizations. To test the mechanism underlying changes in infant gesture production, Study 2 instructed caregivers to respond either contingently or noncontingently to their infants' gestures. Infants given contingent social feedback produced more gestures, more gesture–vocal combinations and used their vocalizations differently compared to infants given noncontingent feedback. Thus, prelinguistic vocal and gesture behavior are mechanistically linked before the first word and should be studied concurrently to understand the development of the communicative system.